Regulations governing student internship programme in Ghana: A sequential explanatory multi-stakeholder approach - Arthur, Patrick; Koomson, Samuel (Utan Kayu Publishing, 2022)
This paper seeks to ascertain the regulations governing student internship programme in Ghana. The sequential explanatory mixed methods approach was utilised. Two separate structured questionnaires were administered to students and senior members (lecturers and administrators) of six selected technical universities (TUs); whereas members of industry, executives of business associations and government regulatory bodies in the tertiary sector of Ghana’s education system were interviewed, using an interview guide. This paper found that no clear legal and regulatory framework govern student internship in Ghana. Specifically, there was no Industrial Training Fund Act in Ghana that promoted and encouraged the acquisition of skills in industry and commerce. Industries were not obliged to accept students for internship. Travel to and from work by interns were not covered by insurance. Students on internship were not covered by the host company’s collective bargaining agreement. There was no well-defined enforceable law requiring TUs to secure internship placement for students, although, some regulatory bodies insisted that TUs showed evidence of their ability to secure placements for their students for industrial training before awarding programme accreditation. There were no penalties levelled TUs who failed to secure internship placements. Interns were largely not covered by any special health insurance package by employers during in cases of injury, theft or death. This paper synchronises the perspectives of multiple actors on the regulations governing student internship programme, presenting useful suggestions which provides information to government, business associations, employers, and TUs for policy planning, formulation and implementation of student internship in Ghana.